Factors influencing the adoption of social networking sites by Malaysian users: an empirical study using structural equation modelling / Muhammad Tahir Jan...[et al.] - Jan, Muhammad Tahir; Abdullah, Kalthom; Momen, Abdul (2014)
The objective of the paper is to determine the factors associated with the adoption of social networking sites for Malaysian Muslim users where it is hypothesized that the thought of the Muslims might differ from others due to their unique religious and social believes.A complete self administered questionnaire was collected from 223 Malaysian Muslim social networking users. Both exploratory and confirmatory factor analysis are used to sort the significant items for the constructs and check the validity where a path model is approached with the use of structural equation model to test the hypothesis.The proposed model acquires the overall goodness-of-fit having the satisfactory results on Normed Chi Square, Comparative Fit Index (CFI) and Root Mean Square Error of Approximation (RMSEA). These results met the cut of values where CFI is more than .90, RMSEA is less than .08 and Normed Chi Square is less than 3. The results of full structural model attest that technological and social factors are the most significant factors behind the adoption of social networking sites among the Malaysian Muslimusers, followed by educational factor. However, the study does not find significant influence of brand or product communication behind this adoption. Since Malaysia is a multi-racial country, a promising future study would be to consider race as a moderating variable in the model of this study.